Chitosan functionalized poly-ε-caprolactone electrospun fibers and 3D printed scaffolds as antibacterial materials for tissue engineering applications - Tardajos, Myriam G.; Gorzelanny, Christian (Carbohydrate polymers, 2018)
Tissue engineering (TE) approaches often employ polymer-based scaffolds to provide support with a view to the improved regeneration of damaged tissues. The aim of this research was to develop a surface modification method for introducing chitosan as an antibacterial agent in both electrospun membranes and 3D printed poly-ε-caprolactone (PCL) scaffolds. The scaffolds were functionalized by grafting methacrylic acid N-hydroxysuccinimide ester (NHSMA) onto the surface after Ar-plasma/air activation. Subsequently, the newly-introduced NHS groups were used to couple with chitosan of various molecular weights (Mw). High Mw chitosan exhibited a better coverage of the surface as indicated by the higher N% detected by X-ray photoelectron spectroscopy (XPS) and the observations with either scanning electron microscopy (SEM)(for fibers) or Coomassie blue staining (for 3D-printed scaffolds). A lactate dehydrogenase assay (LDH) using L929 fibroblasts demonstrated the cell-adhesion and cell-viability capacity of the modified samples. The antibacterial properties against S. aureus ATCC 6538 and S. epidermidis ET13 revealed a slower bacterial growth rate on the surface of the chitosan modified scaffolds, regardless the chitosan Mw.
Gesehen am 09.05.2019